Concept of Punishment - Yolanda Hendartin; Muhammad Faiz Al Maisi; Ananda Tama Rizky; Meldyana Permata Abdillah (Jurnal Sahabat ISNU SU, 2025)
Sentencing is an important part of criminal law. This is because sentencing is the culmination of the entire process of holding someone guilty of committing a crime accountable. "A criminal law without sentencing would more simply be a declaratory system pronouncing people guilty without any formal consequences following that guilt." Criminal law without sentencing means declaring someone guilty without any definite consequences for their guilt. Thus, the concept of guilt has a significant influence on the imposition of punishment and the process of its implementation. If guilt is understood as "blameable," then here punishment is the "embodiment of that blame."